1994
DOI: 10.1007/s001250050089
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-benefit analysis of intensive treatment and teaching programmes for Type 1 (insulin-dependent) diabetes mellitus in Moscow—blood glucose versus urine glucose self-monitoring

Abstract: In a prospective controlled trial the effects of a 5-day in-patient treatment and teaching programme for Type 1 (insulin-dependent) diabetes mellitus on metabolic control and health care costs were studied in Moscow. Two different intervention programmes were compared, one based upon urine glucose self-monitoring (UGSM, n = 61) and one using blood glucose self-monitoring (BGSM, n = 60). Follow-up was 2 years. A control group (n = 60) continued the standard treatment of the Moscow diabetes centre and was follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 15 publications
1
66
0
9
Order By: Relevance
“…Following the selection criteria of the reviews, 16 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] referring to our three reference programmes should have been identified. In practice, a total of 11 were identified [5,28,30,32,34,38,39,[43][44][45][46], and seven [28,32,34,35,38,39,46] were included in at least one of the reviews. In six reviews the main controlled trials of our reference programmes [28, 30-32, 38, 44] were included in data synthesis [10,11,16,18,19,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the selection criteria of the reviews, 16 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] referring to our three reference programmes should have been identified. In practice, a total of 11 were identified [5,28,30,32,34,38,39,[43][44][45][46], and seven [28,32,34,35,38,39,46] were included in at least one of the reviews. In six reviews the main controlled trials of our reference programmes [28, 30-32, 38, 44] were included in data synthesis [10,11,16,18,19,25].…”
Section: Resultsmentioning
confidence: 99%
“…In six reviews the main controlled trials of our reference programmes [28, 30-32, 38, 44] were included in data synthesis [10,11,16,18,19,25]. Out of 25 [5, 33-37, 39, 41-43, 45-59] replication trials (phase 4, see text box: Phases of 'increasing evidence of complex interventions') four [34,35,39,46] were included in six reviews [16,19,21,22,24,25]. Different reviews on identical topics included different publications referring to the same reference programme.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is increasing evidence that intensive insulin therapy is not necessarily associated with a high risk of severe hypoglycaemia [2][3][4][5][6][7]. In the DAFNE trial (Dose Adjustment for Normal Eating), a UK multicentre randomised controlled study, the incidence of severe hypoglycaemia remained unchanged while HbA 1 c and quality of life improved [6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients are taught to match insulin doses to their food choices, while keeping blood glucose close to normal. In several controlled clinical trials the programme has shown sustained improvements in glycaemic control without increasing the risk of severe hypoglycaemia [2][3][4][5]7]. The DTTP has become the standard treatment approach for individuals with type 1 diabetes in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective controlled trial the effectiveness and safety of the inpatient programme was shown at a tertiary diabetes care center in Moscow, Russia [37]. Under the study conditions glucosuria self monitoring was equally effective and safe as blood glucose monitoring and cost effective.…”
Section: Long-term Implementationmentioning
confidence: 99%